Analisis Pendekatan Ekologi dalam Pembelajaran Bahasa Indonesia di Era Digital - Albaburrahim Albaburrahim; Moh. Badruddin Amin (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2024)
This research examines the implementation of an ecological approach in learning Indonesian in the digital era with a focus on the integration of technology and environmental awareness in the learning process. The aim of the research is to analyze Indonesian language learning through an ecological approach in the digital era. The qualitative descriptive research method uses a literature study approach. Data was collected through a literature review which included scientific journals, books, research articles and digital documents relevant to the ecological approach in Indonesian language learning and its application in the digital era. The data obtained was analyzed using content analysis techniques, which included the process of data reduction, data presentation, and drawing conclusions. The research results show, namely. First, the application of an ecological approach in learning Indonesian in the digital era can be done through various digital platforms. Second, digital technology in ecologically based Indonesian language learning offers benefits. Third, ecologically based Indonesian language learning in the digital era requires a change in method, with the teacher as a facilitator who accompanies students to explore and analyze environmental issues through digital language activities.